2018
DOI: 10.1093/rheumatology/key232
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of synovial fluid from osteoarthritic knee and carpometacarpal joints unravels different molecular profiles

Abstract: This study demonstrates that differential expression of molecular players in SF from different OA joints evokes diverse effects on primary chondrocytes. The pathomolecular mechanisms of OA may significantly differ in various joints, a finding that brings a new dimension into the pathogenesis of primary OA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…SF samples of non-erosive OA from the carpometacarpal joints (CMC-I) and of primary idiopathic knee OA patients were investigated by quantitative liquid chromatography mass spectrometry (LC-MS), and revealed multiple peptide differences, including CLU, paraoxonase/arylesterase 1 (PON1) and transthyretin [ 72 ]. In the knee OA group, 28 proteins were up-regulated and 12 down-regulated, as compared to CMC-I group, while 16 of those up-regulated and 3 of down-regulated proteins were linked to inflammatory processes in the joint and lipid transport.…”
Section: Clu As a Translational Biomarker Of Oamentioning
confidence: 99%
See 1 more Smart Citation
“…SF samples of non-erosive OA from the carpometacarpal joints (CMC-I) and of primary idiopathic knee OA patients were investigated by quantitative liquid chromatography mass spectrometry (LC-MS), and revealed multiple peptide differences, including CLU, paraoxonase/arylesterase 1 (PON1) and transthyretin [ 72 ]. In the knee OA group, 28 proteins were up-regulated and 12 down-regulated, as compared to CMC-I group, while 16 of those up-regulated and 3 of down-regulated proteins were linked to inflammatory processes in the joint and lipid transport.…”
Section: Clu As a Translational Biomarker Of Oamentioning
confidence: 99%
“…Higher CLU concentrations (∼1.7-fold increase) were detected in SFs from knee OA patients than in ones from CMC-I OA. These differences in CLU levels might have occurred because the weight-bearing (knee OA) and non-weight bearing (CMC-I) joints were analysed and compared [ 72 ]. Changes in CLU levels in healthy vs .…”
Section: Clu As a Translational Biomarker Of Oamentioning
confidence: 99%
“…Previous studies showed that levels of IL-6 in SF can vary between different joints, which could direct future IL-6 targeted therapy towards relevant patient subgroups. For example, levels of IL-6 were strikingly higher in knee OA SF compared with carpometacarpal joint fluid [ 120 ]. Moreover, more IL-6 was detected in post-traumatic wrist OA compared with knee OA patients [ 121 ].…”
Section: Under Construction: Il-6 Targeted Therapy In Oamentioning
confidence: 99%
“…SF ensures joint lubrication and delivery of nutrients and other essential molecules to articular cartilage 5,6 . A disturbance in SF composition might adversely affect joint homeostasis and result in OA initiation or worsening 3,4,7,8 . In general, OA synovial fluid (OASF) contains increased levels of cytokines, chemokines and damage-associated molecular patterns (DAMPs) 2 .…”
Section: Introductionmentioning
confidence: 99%
“…In line with this, an increased synovial fluid level of vascular endothelial growth factor (VEGF) in OA patients is known to induce vascular hyperpermeability 11 . While the compositional change of SF is evident in OA 12 , only a limited number of studies investigated the direct effects of OASF on chondrocytes 8,13 . Our recent work unraveled the first key underlying mechanisms by which OASF induced chondrocyte dedifferentiation, fibrosis and proliferation 14 .…”
Section: Introductionmentioning
confidence: 99%